Variability in Muscle Adaptation to Electrical Stimulation - Minetto, M. A.; Botter, A.; Bottinelli, O.; Miotti, D.; Bottinelli, R.; D’Antona, G. (International Journal of Sports Medicine, 2013)
The aims were to investigate the plasticity of the myosin heavy chain (MHC) phenotype following neuromuscular electrical stimulation (NMES) and to assess the correlation between MHC isoform distribution and muscle fibre conduction velocity (MFCV).14 men were subjected to 24 sessions of quadriceps NMES. Needle biopsies were taken from the dominant vastus lateralis and neuromuscular tests were performed on the dominant thigh before and after training. NMES significantly increased the quadriceps maximal force by 14.4±19.7% (P=0.02), vastus lateralis thickness by 10.7±8.6% (P=0.01), vastus lateralis MFCV by 11.1±3.5% (P<0.001), vastus medialis MFCV by 8.4±1.8% (P<0.001). The whole spectrum of possible MHC isoform adaptations to training was observed: fast-to-slow transition (4 subjects), bi-directional transformation from MHC-1 and MHC-2X isoforms toward MHC-2A isoform (7 subjects), shift toward MHC-2X (2 subjects), no MHC distribution change (1 subject). No significant correlation was observed between MHC-2 relative content and vastus lateralis MFCV (pre-training: R2=0.04, P=0.46; post-training: R2=0.02, P=0.67). NMES elicited distinct adaptations in the MHC composition and increased force, muscle thickness, and MFCV. The MHC isoform distribution did not correlate with MFCV, thus implying that the proportion of different fibre types cannot be estimated from this electrophysiological variable.
Keywords: electromyography; myosin heavy chain distribution; muscle fibre conduction velocity; muscle thickness; neuromuscular electrical stimulation